Binary categorizations of foods by American, French and Indian adults: Predominance of healthy-unhealthy and minimal emphasis on animal-plant. (1st July 2021) - Rozin, Paul; Holtermann, Callie
Abstract: Objective: Food and drink form a substantial part of health advice, and a significant part of pleasant or unpleasant memories, expectations and experiences. They can be divided into two categories in many ways, and the preferred way in which any person makes this division may be an indicator of how that person thinks about the food-drink domain, with potential health implications. Binary categorization is an uncommon technique but it offers a window into "default" categorization of the world. We employ two different methods to assess binary categorization, spontaneous categorizations, and ranking of a set of defined categorizations. Insofar as these two methods give convergent results, this would serve to strengthen the evidence provided by our findings. Methods: Samples of each of approximately 300 on-line American, French, and Indian adults spontaneously offered a preferred way of dichotomizing the food/drink domain. At a later point in the same questionnaire, they rank ordered the importance to them of each of five categorizations including natural versus processed, animal origin versus plant origin, and healthy versus unhealthy. Results: The predominant categorization by both methods was healthy-unhealthy. The animal-plant origin categorization was rare. The correspondence between results for spontaneous nomination of dichotomies versus ranking a fixed list of dichotomies on importance is substantial, and is a form of validation of the spontaneous method. Discussion: "Healthy-Unhealthy" is a continuum rather than a dichotomy, is subject to changing classifications by the nutrition-medical community, and is limited in value because small amounts of "unhealthy" foods are not unhealthy. In an important sense, "healthy-unhealthy" is an incorrect principle for dividing foods. Surprisingly, only a very small percent of individuals suggested (or ranked highly) animal origin versus plant origin, although this is a true dichotomy, and on biological and nutritional and sustainability grounds, this might be the most fundamental dichotomy.